British poetry and the revolutionary and Napoleonic wars visions of conflict - Bainbridge, Simon, 1965- (Oxford University Press, 2003)
This text argues that poetry played a major role in the mediation of the revolutionary and Napoleonic wars to the British public, and that the wars had a significant impact on poetic practices and theories in the Romantic period.